The urgency of sharia division in Indonesian and Malaysian Islamic bank - Amin Wahyudi; Binti Nur Asiyah; Husnul Haq (Universitas Negeri Surabaya, 2023)
This paper aims to investigate the significance of having a sharia division in Indonesian and Malaysian Islamic banks. This paper is a qualitative study based on a review of official documents from the Indonesian Central Bank and the Indonesian Sharia Council. Interviews with Sharia Advisers were conducted to conduct an interpretive, critical, and descriptive study of the issue. The interpretive analysis was carried out by interpreting each issued regulation, and the analysis was deepened by presenting a description of the sharia division's implementation in Malaysian Islamic banks. Efforts to analyze the results are carried out by reducing the information obtained, presenting the data and concluding. According to the research findings, there are numerous deviations in non-compliance with Sharia implementation in disbursed financing. According to the findings, Islamic banks must have a Sharia division in their organisational structure. The Sharia division ensures that Sharia bank operations follow Sharia principles, beginning with input, processing, and output. This study's theoretical implication is a study of sharia implementation by providing a sharia division in the organisational structure of Islamic banks. This is a more extensive study involving more sharia banks on their willingness and the internal awareness of the presence of the sharia division. Any country that wishes to establish sharia banks must research the presence of sharia divisions to ensure sharia compliance in their operations.